Multiple Omics Integration Reveals Key Circular RNAs in Hepatocellular Carcinoma - Huang, Zi-Li; Huang, Xiu-Yan; Huang, Jin; Huang, Xin-Yu; Xu, Yong-Hua; Zhou, Jian; Tang, Zhao-You (Frontiers in Oncology, 2021)
BACKGROUND HCC is one of the most common malignancies with an increasing incidence worldwide, especially in Asian countries. However, even though targeted cancer therapy drugs such as sorafenib and regorafenib are available, the overall outcome of HCC remains unsatisfactory. Thus, it is urgent to investigate the molecular mechanisms of HCC progression, so as to provide accurate diagnostic criteria and therapeutic targets. METHODS RNA-seq data was used to identify and quantify circRNA. DESeq2 was used to identify the differentially expressed circRNAs. miRNA binding sites within circRNAs were identified by miRanda. Gene set enrichment analysis (GSEA) was conducted to predict the biological function of circRNAs. RESULTS The differential expression analysis identified 107 upregulated and 95 downregulated circRNAs in HCC tissues, of which, circZKSCAN1 was reported to inhibit hepatocellular carcinoma cell growth, migration, and invasion through several cancer-related signaling pathways. We also observed that a DE-circRNA, chr2:65318117|65325200 was highly negatively correlated with its parental gene RAB1A (PCC < -0.6), which was also closely associated with mTOR signaling pathway. Moreover, we also constructed competing endogenous RNA (ceRNA) network to identify key circRNAs involved in HCC. Notably, hsa_circ_0002130 and hsa_circ_0008774 were highly correlated with the genes involved in gluconeogenesis and HNF3A pathway via the target genes, GOT2 and AR, suggesting that the two circRNAs might regulate these pathways, respectively. Survival analysis of the two circRNA target genes revealed that GOT2 and AR were both associated with favorable prognosis. CONCLUSION In summary, the circRNAs highlighted by the integrative analysis greatly improved our understanding of the underlying mechanism of circRNAs in HCC.